Knowledge of Latin American Obstetricians and Gynecologists regarding Heavy Menstrual Bleeding - Luis Bahamondes; Victor Marin; Silvia Ciarmatori; Agnaldo L. Silva-Filho; Juan Manuel Acuña; Maria Y. Makuch (Obstetrics and Gynecology International)
Background. Heavy menstrual bleeding (HMB) is a common gynecological complaint affecting quality of life. Objectives. To assess knowledge on diagnosis and treatments of HMB of Latin American (LA) obstetricians and gynecologists (OBGYNs). Methods. A survey was conducted during a scientific meeting, organized to provide updated information on topics of reproductive medicine to OBGYNs from 12 LA countries who were invited to respond to a multiple-choice questionnaire. Results. Of the 210 OBGYNs participating in the survey, from 169 (80.4%) to 203 (96.7%) answered the questions. Most respondents (80%) gave accurate answers regarding the amount of blood loss which defines HMB, underreported the proportion of women who consulted due to HMB, and were aware that the use of combined oral contraceptives (COCs) with ethynyl estradiol is not an adequate treatment in women with HMB. Female OBGYNs and those who worked in the private sector were more prone to report a higher possibility of improvement of HMB with a COC that contained estradiol valerate and dienogest or with a levonorgestrel-releasing intrauterine system. Conclusions. In general, the respondents were aware of the importance of HMB in gynecological practice and of the new medical treatments and underreported the proportion of women who consulted due to HMB.